2000
DOI: 10.1093/toxsci/55.2.468
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sulfur, Thiol, and Thiol Inhibitor Compounds on Arsine-Induced Toxicity in the Human Erythrocyte Membrane

Abstract: The mechanism of arsine (AsH(3)) toxicity is not completely understood. The first cytotoxic effect of AsH(3) is disruption of ion homeostasis, with a subsequent hemolytic action. The only accepted treatment for AsH(3) toxicity is exchange transfusion of the blood. In this study the effect of sulfur, sulfur compounds, thiol-containing compounds, and thiol inhibitors on AsH(3)-induced disruption of membrane transport and hemolysis in human erythrocytes was investigated in vitro. Elemental sulfur, sodium thiosulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Experiments on red blood cells exposed to arsine gas showed that arsine depleted the reduced glutathione content of the red blood cells, resulting in an oxidation of sulfhydryl groups in hemoglobin and red cell membranes, producing membrane instability with rapid intravascular hemolysis (25). Later investigations have proposed a non-oxidant mechanism by suggesting that the target site for arsine is the sodiumpotassium pump on the membrane (7,26). Recently, it has been reported that the interaction between arsine and hemoglobin results in an increase in heme release which may contribute to the hemolytic mechanism of arsine (27).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on red blood cells exposed to arsine gas showed that arsine depleted the reduced glutathione content of the red blood cells, resulting in an oxidation of sulfhydryl groups in hemoglobin and red cell membranes, producing membrane instability with rapid intravascular hemolysis (25). Later investigations have proposed a non-oxidant mechanism by suggesting that the target site for arsine is the sodiumpotassium pump on the membrane (7,26). Recently, it has been reported that the interaction between arsine and hemoglobin results in an increase in heme release which may contribute to the hemolytic mechanism of arsine (27).…”
Section: Discussionmentioning
confidence: 99%
“…Blair et al (1990a,b) exposed male and female mice to arsine at concentrations totaling 9-900 ppm administered for 6 h/ day for 5 days over 13 weeks. This conclusion was corroborated to some extent by the addition of the sulfhydryl inhibitor N-ethylmaleimide, 2 h after arsine exposure, which resulted in less hemolysis (Rael et al, 2000). Between 15 and 90 days, a regenerative process appeared to have been activated by elevated reticulocytes and mean corpuscular volume.…”
Section: Exposure Biochemistrymentioning
confidence: 74%
“…In an in vitro study, a decrease in reduced GSH concentration in human RBCs was found to correlate with the hemolytic action of arsine (Rael et al, 2000). Blair et al (1990) recorded a 60% decrease in reduced GSH level in erythrocytes exposed to arsine in vitro.…”
Section: Mechanism Of Toxicitymentioning
confidence: 96%
“…Oxyhemoglobin (oxyHb) has been recognized as a necessary component for overall mechanism of AsH 3 -induced hemolysis, as conversion of oxyHb to carboxyHb prevents hemolysis in erythrocytes exposed to AsH 3 (Rael et al, 2000).…”
Section: Mechanism Of Toxicitymentioning
confidence: 99%